Determination of acidity constants and ionic mobilities of polyprotic peptide hormones by CZE - Šolínová, Veronika; Kašička, Václav (Electrophoresis, 2013)
CZE has been applied to determination of thermodynamic acidity constants (pKa ) of ionogenic groups and actual ionic mobilities of polyprotic peptides-synthetic human and salmon gonadotropin-releasing hormones and their derivatives and fragments. First, the mixed acidity constants, pKa,imix, of ionogenic groups, and actual ionic mobilities, mi , of gonadotropin-releasing hormone peptides were determined by nonlinear regression analysis of pH dependence of their effective electrophoretic mobilities. The effective mobilities were measured by CZE in a series of BGEs within a broad pH range (1.80-12.10), at constant ionic strength (25 mM) and reference temperature (25°C). Second, the pKa,imix values were recalculated to thermodynamic pKa s using the Debye-Hückel theory. Thermodynamic pKa of carboxyl groups was estimated to be in the range of 2.5-3.3 for C-terminal amino acids of the above peptides, and 5.2 for glutamic acid in the middle of peptide chain; pKa of imidazolyl group of histidine residues was in the range of 5.7-6.8, pKa of N-terminal amino group of the peptide with free N-terminus was equal to 6.2, pKa of phenol group of tyrosine residues was in the range of 9.8-10.8, and pKa of guanidinyl group or arginine residues reached values 11.1-11.3, depending on the position of the residues in the peptide and on the amino acid sequence of the peptide. Absolute values of actual ionic mobilities of peptides with charge number ±2 were in the range (14.6-18.6) × 10(-9) m(2) V(-1) s(-1) , and ionic mobilities of peptides with charge number ±1 reached values (6.5-12.9) × 10(-9) m(2) V(-1) s(-1) .
Keywords: termodynamika; pKa; Acid dissociation constant; Gonadotropin-releasing hormones; Nonlinear Dynamics; koncentrace vodíkových iontů; nelineární dynamika; Salmon; Ions; Gonadotropin-Releasing Hormone; elektroforéza kapilární; hormon uvolňující gonadotropiny; ionty; losos; Peptides; Thermodynamics; zvířata; Humans; Hydrogen-Ion Concentration; Electrophoresis, Capillary; Ionization constant; lidé; Animals